2009
DOI: 10.1039/b910049k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium complexes containing novel cyclic selenium imides

Abstract: The first metal complexes of cyclic selenium(II) imide ligands, [PdCl2{Se,Se'-Se4(NtBu)3}] and [PdCl2{Se,Se'-Se4(NtBu)4}], which are obtained from the reaction of Se(NtBu)2 with [PdCl2(NCPh)2], contain the novel Se-N heterocycles Se4(NtBu)3 and Se4(NtBu)4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…shown by 125 Te NMR to adopt a butterfly structure with exo Te atoms. 80 A number of studies have reported the oxidation of P(III) to P(V) by a range of chalcogen sources; reaction of RPCl 2 (R = Me, Et, i Pr, t Bu, Ph, Ad, 2-thiophenyl) with M 2 Se and M 2 Se 2 (2 : 2 : 1) afforded [(RP) 2 Se 4 ]M 2 (M = Li, Na).…”
Section: àmentioning
confidence: 99%
“…shown by 125 Te NMR to adopt a butterfly structure with exo Te atoms. 80 A number of studies have reported the oxidation of P(III) to P(V) by a range of chalcogen sources; reaction of RPCl 2 (R = Me, Et, i Pr, t Bu, Ph, Ad, 2-thiophenyl) with M 2 Se and M 2 Se 2 (2 : 2 : 1) afforded [(RP) 2 Se 4 ]M 2 (M = Li, Na).…”
Section: àmentioning
confidence: 99%
“…7 Cyclic selenium imides; Se4(N t Bu)3 (17) is only known as a ligand in a metal complex (Section 3.6). 41 This journal is © The Royal Society of Chemistry 20xx…”
Section: Figmentioning
confidence: 99%
“…46 The seven-membered ring Se4(N t Bu)3 (17) depicted in Fig. 5 has not been isolated in the reaction of SeCl2 with t BuNH2, however it has been identified in the palladium complex [PdCl217], which is formed in small amounts, together with [PdCl219] from the reaction of t BuN=Se=N t Bu with PdCl2(NCPh)2 in THF for 16 h. 41 In a separate experiment it was shown by 77 Se NMR spectroscopy that the six-membered ring Se3(N t Bu)3 (13) is transformed into the corresponding cyclic tetramer Se4(N t Bu)4 (19) in the presence of [PdCl2(NCPh)2], suggesting that ring transformations of the cyclic selenium imides may be promoted in the presence of a metal centre. 41 The seven-membered Se4(N t Bu)3 ring in [PdCl217] is Se,Sechelated to palladium via the selenium atoms that have two nitrogen neighbours, while the bidentate coordination mode for the eight-membered Se4(N t Bu)4 ring in [PdCl219] involves two antipodal selenium atoms (Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular structure of the complex in (35), (tris(t-butylimido)tetraselane)-dichlorido-palladium benzonitrile solv- ate [53], features a buckled, seven-membered [SeNSe 2 NSeN] ring with two selenium(II) atoms coordinated to a palladium atom. One of the non-coordinating selenium(II) atoms forms a Se(lp)···π(arene) interaction with the benzonitrile ring [d = 3.57 Å and θ = 14.4°] (Figure 14.17c).…”
Section: Selenium(ii)mentioning
confidence: 99%